2017
DOI: 10.1016/j.ejphar.2017.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of liver fibrosis in patients with HBV-related chronic liver disease undergoing antiviral treatment: A preliminary study

Abstract: In chronic hepatitis B (CHB) patients, fibrosis assessment during antiviral treatment is a key step in the clinical management. Aim of this study was to evaluate the performance of elastography in assessing fibrosis stage in CHB before and after two years of nucleoside/nucleotide analogues (NUC) treatment in comparison with indirect serum markers. CHB diagnosis was made according to standard criteria. A clinical and virological evaluation was performed at baseline and again at 3, 6, 9, 12 18, and 24 months dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
(8 reference statements)
0
15
2
Order By: Relevance
“…Although AST-to-platelet ratio index and FIB-4 index are associated with significant fibrosis and cirrhosis in patients with chronic hepatitis B before antiviral therapy (16), AST-to-platelet ratio index and FIB-4 have been proven not suitable for the evaluation of fibrosis improvement in chronic hepatitis B patients receiving antiviral therapy (25). On the other hand, serial tissue elastography examinations by FibroScan correlate well with the regression of liver fibrosis after antiviral therapy (26), and liver fibrosis improves significantly after 5-year antiviral therapy as monitored by FibroScan in chronic hepatitis B patients with advanced fibrosis (27). However, there were no nontreatment groups (as control) for comparison in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although AST-to-platelet ratio index and FIB-4 index are associated with significant fibrosis and cirrhosis in patients with chronic hepatitis B before antiviral therapy (16), AST-to-platelet ratio index and FIB-4 have been proven not suitable for the evaluation of fibrosis improvement in chronic hepatitis B patients receiving antiviral therapy (25). On the other hand, serial tissue elastography examinations by FibroScan correlate well with the regression of liver fibrosis after antiviral therapy (26), and liver fibrosis improves significantly after 5-year antiviral therapy as monitored by FibroScan in chronic hepatitis B patients with advanced fibrosis (27). However, there were no nontreatment groups (as control) for comparison in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with infectious hepatitis, nonalcoholic fatty liver disease, and alcoholic liver disease, composite models comprised of laboratory values, patient characteristics, and hepatic elastography either by magnetic resonance or ultrasound, have been developed primarily to predict the presence of cirrhosis . However, to the best of our knowledge, there are only two post‐Fontan reports, with 10 patients each, that have compared liver biopsy findings with either magnetic resonance or ultrasound hepatic elastography .…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding its limitations, secondary to sampling and intraobserver and interobserver variations, liver biopsy is the accepted gold standard for determining the degree of hepatic fibrosis, regardless the etiology; nevertheless, a noninvasive method that correlates with the degree of liver fibrosis would be a more practical clinical approach. Previous, large patient cohort studies report correlations between liver pathology and noninvasive methods, including composite models comprised of multiple patient variables, in those with infectious hepatitis, nonalcoholic fatty liver disease, and alcoholic liver disease . However, there are few reports comparing liver biopsy findings with noninvasive approaches in patients with Fontan associated liver disease (FALD); thus, there are no current, useful, clinic‐based, noninvasive methods that strongly correlate one with the other .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(15)(16)(17)(18)(19)(20)(21) Most of these co-infected patients are on combination antiretroviral therapy (cART), which includes medications that suppress HBV and may affect the performance of noninvasive tests. (22) Although several studies have reported a single noninvasive marker of fibrosis in HBV-HIV subjects on cART, (23)(24)(25)(26)(27) few investigations have evaluated the discriminatory capacity of noninvasive markers (i.e., with comparisons to liver histology as the gold standard) in this special population, (28)(29)(30) and only one has compared the relative discriminatory capacity of APRI and FIB-4, the two most widely used serum-based markers, to VCTE. (31) Although most HBV-HIV co-infected subjects on cART have suppressed HBV DNA and normal liver enzymes, we have previously shown that a high proportion can have significant underlying fibrosis.…”
mentioning
confidence: 99%